The relationship between innovation performance and innovation competency among tourism small and medium enterprise in Terengganu - Nurin Hazirah Razdi; Nur Fatihah Azmi; Najwa Nasuha Mohd Nordin; Nur Atiqah Abdul Rahman (2021)
This study is about the relationship between innovation competency and innovation performance among TSME in Terengganu. In order to improve innovation performance, there is an emphasis on leadership competency, owner attributes competency, and networking competency. A quantitative study is used to accomplish this research. Simple random sampling is used and responses from 379 respondents are collected. To analyze all the data, descriptive analysis, reliability testing, and Pearson correlation are used. The results support all the variables. This research contributes to determinants of the relationship between innovation competency and innovation performance among TSME in Terengganu. This research and data can be used by industry stakeholders to provide a better experience by determining the association between innovation competency and innovation performance among TSME in Terengganu.